2022
DOI: 10.1155/2022/5355286
|View full text |Cite|
|
Sign up to set email alerts
|

Research on Probability Distribution of Short-Term Photovoltaic Output Forecast Error Based on Numerical Characteristic Clustering

Abstract: The forecast error characteristic analysis of short-term photovoltaic power generation can provide a reliable reference for power system optimal dispatching. In this paper, the total in-day error level was stratified by fuzzy C-means algorithm. Then the historical PV output data based on the numerical characteristics of point prediction output were classified. A General Gauss Mixed Model was proposed to fit the forecast error distribution of various photovoltaic output forecast error distribution. The impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Then, Wu et al [42] developed a mixed LaPlace-Gaussian distribution to model persistence-based forecasts for wind power. While Yan et al [43] consider analysing PV power forecasting error distribution using a Gauss model. Note that the common limitation of the aforementioned work is to limit their analysis to few distributions, or to develop complex tailor-made solutions.…”
Section: Scenario Characterisationmentioning
confidence: 99%
“…Then, Wu et al [42] developed a mixed LaPlace-Gaussian distribution to model persistence-based forecasts for wind power. While Yan et al [43] consider analysing PV power forecasting error distribution using a Gauss model. Note that the common limitation of the aforementioned work is to limit their analysis to few distributions, or to develop complex tailor-made solutions.…”
Section: Scenario Characterisationmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%